Health Belief Model Towards the Utilization of Acetic Acid Visual Inspection Method as an Early Detection Program for Cervical Cancer - Juwita, Linda; Perwiraningtyas, Pertiwi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Cervical cancer is a disease with high morbidity and mortality rates and ranks 4th highest in the world. Most people are not yet aware of the importance of early detection of cervical cancer, one of which is by visual inspection of acetic acid. The Health Belief Model Theory is needed to make people aware of the importance of Visual Inspection of Acetic Acid. The purpose of this study was to analyze the relationship between the health belief model and early detection of cervical cancer using the visual inspection method of acetic acid. The research design used was a cross-sectional design with a population of all integrated service post cadres in the Jagir Surabaya Health Center working area totaling 84 people. The sampling technique was purposive sampling. The sample consisted of 70 people with the criteria of being married and/or having had sexual intercourse. The instruments used were the Health Belief Model questionnaire and the Visual Inspection of Acetic Acid questionnaire. The analysis test used the Chi-square test, and the Fisher’s exact test as an alternative test, which obtained a p value of 0.714 for susceptibility, 1.000 for seriousness and severity, 0.767 for benefits and 1.000 for obstacles. The results of the study showed no significant relationship between vulnerability, seriousness and severity, benefits and barriers to the use of early detection of the IVA method. So that multivariate testing cannot be carried out. The follow-up plan for further research is to provide interventions for women of childbearing age in order to improve health behavior in early detection of cervical cancer with routine Acetic Acid Inspection examinations.